The Influence of Personal Technical Skills, Management Participation, and The Utilization of Information Technology on The Effectiveness of Accounting Information Systems - Ni Made Dwika Putri; Gede Juliarsa (International Journal of Economics, Commerce, and Management, 2025)
Improving financial management effectiveness in cooperatives, particularly Savings and Loans Cooperatives, can be better achieved through the implementation of an accounting information system. The effectiveness of an accounting information system refers to the extent to which the system can collect, process, store data, and provide information and reports in a timely manner. This study aims to examine the influence of personal technical skills, management participation, and the utilization of information technology on the effectiveness of accounting information systems. The sample consisted of 118 cooperative employees who use information systems in their daily work, selected using a purposive sampling method. Data collection was conducted through a questionnaire, and the analytical technique used was multiple linear regression analysis. The results show that personal technical skills, management participation, and the utilization of information technology have a significant positive effect on the effectiveness of accounting information systems. This study provides empirical evidence supporting the Technology Acceptance Model (TAM), which explains that the acceptance of a technology is mainly influenced by two key factors: perceived ease of use and perceived usefulness.